Mesenchymal Stem Cells Derived Extracellular Vesicles Alleviate Traumatic Hemorrhagic Shock Induced Hepatic Injury via IL-10/PTPN22-Mediated M2 Kupffer Cell Polarization - Zhang, Yunwei; Zhang, Xiaofei; Zhang, Hongji; Song, Peng; Pan, Wenming; Xu, Peng; Wang, Guoliang; Hu, Ping; Wang, Zixuan; Huang, Kunpeng; Zhang, Xiaodong; Wang, Hui; et al. (Frontiers in Immunology, 2022)
Traumatic hemorrhagic shock (THS) is a major cause of mortality and morbidity worldwide in severely injured patients. Mesenchymal stem cells (MSCs) possess immunomodulatory properties and tissue repair potential mainly through a paracrine pathway mediated by MSC-derived extracellular vesicles (MSC-EVs). Interleukin 10 (IL-10) is a potent anti-inflammatory cytokine that plays a crucial role during the inflammatory response, with a broad range of effects on innate and adaptive immunity, preventing damage to the host and maintaining normal tissue homeostasis. However, the function and mechanism of IL-10 in MSC-mediated protective effect in THS remain obscure. Here, we show that MSCs significantly prolong survival and attenuate hepatic injury and inflammation from THS in mice. Notably, these beneficial effects of MSCs disappeared when IL-10 was knocked out in EVs or when recombinant IL-10 was administered to mice. Mechanistically, MSC-EVs function to carry and deliver IL-10 as cargo. WT MSC-EVs restored the function of IL-10 KO MSCs during THS injury. We further demonstrated that EVs containing IL-10 mainly accumulated in the liver during THS, where they were captured by Kupffer cells and induced the expression of PTPN22. These effects subsequently shifted Kupffer cells to an anti-inflammatory phenotype and mitigated liver inflammation and injury. Therefore, our study indicates that MSC-EVs containing IL-10 alleviate THS-induced hepatic injury and may serve as a cell-free therapeutic approach for THS.